(untitled) (Research, Society and Development, 2020)
Pest insects represent an important source of agricultural losses across the globe. This situation is maximized by the introduction of species outside their natural area of occurrence, leading countries to draw up quarantine lists in order to protect their domestic production and not compromise their exports of agricultural products. In this sense, this research seeks to analyze the invasive potential and risks of Bactrocera carambolae Drew & Hancock 1994 (Diptera: Tephritidae), an important pest of world fruit and quarantine pest present in Brazil. Bactrocera carambolae is a species of fruit fly from Southeast Asia that infests a great diversity of fruit, both native and of economic interest. In Brazil, its entry is dated 1996 in the state of Amapá, and currently beyond that state, it was reported in the states of Pará and Roraima. Here it already infests 21 hosts, among them acerola, star fruit, cashew, guava, mango and tangerine, and has the potential to enter important agricultural markets, such as the irrigated fruit pole in the São Francisco Valley. Bactrocera carambolae poses serious risks for Brazilian fruit production, mainly due to the potential exclusion of markets for fruit exports. Thus, actions to control and eradicate this pest need to be maintained and improved, seeking to avoid severe socioeconomic damage to the fruit production chain in Brazil.